The Representation of speech events in Chariton's Callirhoe and the Acts of the Apostles - Smith, Adrian T. (Linguistic Biblical Studies, 2014)
In The Representation of Speech Events in Chariton's Callirhoe and the Acts of the Apostles , Adrian T. Smith summarizes cross-linguistic research on how and why narrators vary the formulae that introduce direct speech. This research is applied to Chariton and to Acts. The findings demonstrate that narrators vary quotation formulae for numerous pragmatic purposes, including the tracking of conversational dynamics via a set of 'marked' and 'unmarked' quotation devices.